Facial Trauma in Sports: Review and Return-to-Play - Teresa Gomes Silva; Manuel Neiva Sousa; Maria Oliveira Santos; Cátia Mateus; Pedro Gomes de Oliveira (Gazeta Médica, 2023)
Maxillofacial trauma can occur with high frequency while playing sports. Skeletal and soft tissue lesions can occur, with different degrees of severity and impact for the athlete. Sports-related facial fractures most frequently affect the nose, zygoma and mandible, regardless of the country and sport. During initial evaluation it is important to distinguish between stable injuries that can be treated on the sidelines or after the match and emergencies requiring prompt hospital transfer. Athletes could benefit from a more personalized approach to treatment, aimed at optimizing the timeframe for return to play. There is a lack of evidence-based studies on return to play after facial trauma, and currently no specific guidelines exist. Return to sport depends on a variety of factors, such as type of fracture, the risk of impact within the sport, the player’s motivation for an early return and the surgeon’s knowledge and experience.